2009
DOI: 10.1021/bi801218n
|View full text |Cite
|
Sign up to set email alerts
|

An Autocatalytic Mechanism for NiFe-Hydrogenase: Reduction to Ni(I) Followed by Oxidative Addition

Abstract: The mechanism for H(2) cleavage in NiFe-hydrogenase has been reinvestigated with large models using both hybrid DFT by itself, or in a QM/MM scheme following the ONIOM approach. Heterolytic cleavage, with one hydrogen ending up as a bridging hydride and one as a proton on a cysteine ligand, was found to have a barrier slightly too high to be compatible with measured catalytic turnover rates. Alternative mechanisms were therefore investigated. In the finally suggested mechanism, heterolytic cleavage is used onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 48 publications
5
103
0
Order By: Relevance
“…[90,99] Ni-R can exist in up to three different protonation states, while several transition states have been proposed in order to account for a heterolytic splitting of dihydrogen. In this context, an ONIOM theoretical study suggested the possibility of a Ni 1 + species that can bind two hydrides leading to Ni 3 + and then results in a Ni 2 + with a hydride bridge for Ni-R. [115] More recently, a series of possible structural models for the different Ni-R forms of the D. vulgaris MF has been constructed on the basis of a comparison with synthetic Ni-Ru complexes that can perform heterolytic splitting of H 2.…”
Section: The Fully Reduced State(s) Ni-rmentioning
confidence: 99%
See 1 more Smart Citation
“…[90,99] Ni-R can exist in up to three different protonation states, while several transition states have been proposed in order to account for a heterolytic splitting of dihydrogen. In this context, an ONIOM theoretical study suggested the possibility of a Ni 1 + species that can bind two hydrides leading to Ni 3 + and then results in a Ni 2 + with a hydride bridge for Ni-R. [115] More recently, a series of possible structural models for the different Ni-R forms of the D. vulgaris MF has been constructed on the basis of a comparison with synthetic Ni-Ru complexes that can perform heterolytic splitting of H 2.…”
Section: The Fully Reduced State(s) Ni-rmentioning
confidence: 99%
“…H 2 , H À ) bound to the active site. [31,91] All details of the mechanism are not yet available, a fact that has led to several mechanistic proposals [11,31,32,93,94,115] . An interesting alternative to the above discussed scheme has been postulated, in which only the Ni-R and Ni-C states are involved in catalysis, except for other (more reduced) transient species.…”
Section: The Catalytic Mechanism Of [Nife] Hydrogenases and The Inhibmentioning
confidence: 99%
“…However, the chemical identities of these states as well as the catalytic mechanism of hydrogenases are still under debate. Quantum mechanics studies provide the most detailed insight into the mechanism and its intermediates [40][41][42][43][44], but no detailed study exists for [NiFeSe] hydrogenases. Therefore, in this work, we chose to assume that the mechanism and the intermediates proposed for [NiFe] hydrogenases can be transposed to [NiFeSe] hydrogenases, given their similarity.…”
Section: Preparation Of the Crystallographic Structurementioning
confidence: 99%
“…H2, CO2, CH4, NH3, HPO4 2-and HS -/ H2S) (Fuchs 1989(Fuchs , 2011Berg et al, 2010;Say and Fuchs, 2010). The electron transfer proteins involved in the generation of the proton motive force -many of which host inorganic metal sulfide-containing active centers -have been suggested to be amongst the most ancient catalysts (Eck and Dayhoff, 1966;Baymann et al 2003;Schoepp-Cothenet et al, 2013;Volbeda and Fontecilla-Camps, 2006;Vignais and Billoud, 2007;Lill and Siegbahn, 2009;McGlynn et al, 2009;.…”
Section: Introductionmentioning
confidence: 99%